Recent trends in template assisted 3D porous materials for electrochemical supercapacitors. Issue 45 (11th November 2021) - Swain, Nilimapriyadarsini; Saravanakumar, Balasubramaniam; Kundu, Manab; Schmidt-Mende, Lukas; Ramadoss, Ananthakumar
Abstract : This review delivers a comprehensive overview of the various experimental approaches used to fabricate three-dimensional porous materials decorating with organic and inorganic materials for supercapacitor applications. Abstract : Supercapacitors have emerged as an outstanding candidate among numerous energy storage devices because of their long-term cycle life, high power density, and minimal safety concerns. As we know, the lower energy density of supercapacitors hindered their practical applications. Therefore, extensive research efforts have been devoted to exploring various nanostructured three-dimensional electrode materials to overcome this obstacle. To achieve a larger surface area, shorter ion-diffusion path, faster ion accessibility, and higher conductivity, most researchers developed template-assisted 3D architecture designed electrodes. Based on the current research trends, we have reviewed recent advances in the fabrication of hierarchically three-dimensional porous materials via various experimental strategies for supercapacitors. Particularly, hydrogen bubble dynamic template (HBDT), anodic aluminium oxide (AAO), and metal–organic framework (MOF) based approaches have been extensively reviewed. Various experimental parameters, which control the morphology of 3D structures, are summarized. Moreover, the electrochemical performance analysis of template-assisted 3D architecture electrodes for supercapacitor applications with their pros and cons is discussed. Various research studies have showed that higher energy and power performance can be achieved based on a conductive network, shorter diffusion path length, large active surface area, tuneable morphological, 3D porous network, etc. Therefore, the 3D template approach could lead to positive steps towards higher energy and power performance. Also, the present review demonstrates that binder and conductive additive-free 3D porous electrodes open up a new avenue to fabricate high surface area electrodes for improved charge storage performance. Finally, the challenges and future direction of 3D porous-based electroactive materials for supercapacitors were also discussed.